J. Rasmus Brandt, Erika Hagelberg, Gro Bjørnstad and Sven Ahrens (eds), Life and Death in Asia Minor in Hellenistic, Roman and Byzantine Times: Studies in Archaeology and Bioarchaeology - Jongman, Willem M. (Journal of Greek Archaeology, 2021)
In one of the most important works of historical scholarship of the last century, Peter Laslett gave a chilling sketch of The World We Have Lost. The book built on the recent advances in historical demography and family reconstitution to describe a preindustrial society where the Grim Reaper was omnipotent, with average life expectancies at birth of 20-35 years, high infant mortality, cruelly interrupted marriages, and many orphaned children. It was a fitting antidote to romantic views of a past where everything was somehow comfortably better. For the ancient world, such family reconstitutions were impossible for lack of suitable sources.